Direct Visualization and Identification of Membrane Voltage‐Gated Sodium Channels from Human iPSC‐Derived Neurons by Multiple Imaging and Light Enhanced Spectroscopy. Issue 7 (20th May 2022) - Moretti, Manola; Limongi, Tania; Testi, Claudia; Milanetti, Edoardo; De Angelis, Maria Teresa; Parrotta, Elvira I.; Scalise, Stefania; Santamaria, Gianluca; Allione, Marco; Lopatin, Sergei; Torre, Bruno; Zhang, Peng; et al.
Abstract: In this study, transmission electron microscopy atomic force microscopy, and surface enhanced Raman spectroscopy are combined through a direct imaging approach, to gather structural and chemical information of complex molecular systems such as ion channels in their original plasma membrane. Customized microfabricated sample holder allows to characterize Nav channels embedded in the original plasma membrane extracted from neuronal cells that are derived from healthy human induced pluripotent stem cells. The identification of the channels is accomplished by using two different approaches, one of them widely used in cryo‐EM (the particle analysis method) and the other based on a novel Zernike Polynomial expansion of the images bitmap. This approach allows to carry out a whole series of investigations, one complementary to the other, on the same sample, preserving its state as close as possible to the original membrane configuration. Abstract : A method to direct image and characterize ion channels in their native cell membrane by TEM, AFM, and Raman spectroscopy.